Structural health monitoring based on piezoelectric transducers: Analysis and design based on the electromechanical impedance - Baptista, Fabricio G. [UNESP]; Filho, Jozue Vieira [UNESP]; Inman, Daniel J. (Taylor & Francis, 2017)
Piezoelectric transducers are widely used in many applications. In recent years, these transducers have been used in a modern and promising application: structural health monitoring (SHM) of various types of structures.